Impact of Level of Pediatric Amputation on Selection of Prosthetic Component Options. Issue 1 (January 2022) - Nemade, Amit; Miller, Freeman; Thacker, Mihir; Oleas-Santillan, Geovanny; Rogers, Kenneth J.
ABSTRACT: Introduction: Amputation is one of the oldest surgeries known to the human race. The principles of amputation in children are different than in adults. Common indications for amputation include congenital, traumatic, infection, malignancy, vascular, and other pathology. Improper prosthetic fitting or inability to use the most modern available prosthesis can lead to dissatisfaction and compromised high-level function. The aim of this study was to assess residual limbs for compatibility to fit the most modern prosthetic components. Methods: This study is a retrospective review of medical records of patients who underwent amputation between the pelvis and midfoot before 18 years of age. Age, sex, etiology, and level of amputation were recorded. A senior certified prosthetist graded the limbs based on limitations the residual limb imposed on options for the highest functioning modern prosthetic components. Results: Sixty-one patients were identified (35 male, 26 female) with a mean age at assessment of 17.35 years (range, 1.86–35.35 years). Congenital causes and tumors were the most common etiology. Amputations around the ankle were most common (25), followed by transtibial (20). There were 59% grade 1 limbs with no restrictions to component options, 28% grade 2 with moderate restrictions, and 13% grade 3 or severely limited component options due to the residual limb. Most grade 1 residual limbs were transtibial or proximal. Amputations distal to transtibial were of all grades. Conclusions: The choices for optimal high-level prosthetic components are much less limited for transtibial amputation than more distal amputations leading to potentially less high-level prosthetic function. Managing the residual limb length and prosthetic fitting ability is an important element in pediatric amputations if the goal is to fit mature young adults with the highest functioning level prosthetic components.